High-involvement human resource management practices and employee resilience: The mediating role of employee technology adaptation. A case study of South Sumatra - Afriyadi Cahyadi; Taufiq Marwa; József Poór; Ahmad Maulana; Katalin Szabó (Administrative Sciences, 2024)
In the post-COVID-19 era, the need for a resilient workforce to maintain a competitive advantage has become increasingly critical. Despite advancements, there is a research gap in understanding how employee resilience is influenced by high-involvement human resource management practices and employee technology adaptation. This study addresses this gap by developing and empirically testing a mediation model linking to employee technology adaptation and resilience. Theoretical frameworks include the resource-based view, human co-adaptation, and positive organizational behavior. A cross-sectional survey of 322 employees from small and medium enterprises in South Sumatra was conducted. Structural equation modeling was used to analyze the mediating role of employee technology adaptation in the relationship between high-involvement human resource management practices and employee resilience. The results indicate that high-involvement human resource management practices positively affects both technology adaptation and resilience. Employee technology adaptation partially mediates this relationship. The findings offer practical insights for human resource managers, suggesting that fostering technology adaptation through high-involvement human resource management practices can enhance employee resilience. This study concludes with a discussion on the theoretical and practical implications contributing to the development of small and medium enterprises in the digital era post COVID-19.
Keywords: 350; high-involvement human resource management practices; employee technology adaptation; employee resilience; post-COVID-19 era; small and medium enterprises